Total Flavonoids of Litchi Seed Attenuate Prostate Cancer Progression Via Inhibiting AKT/mTOR and NF-kB Signaling Pathways - Chang, Ming; Zhu, Dan; Chen, Yanjiang; Zhang, Weiquan; Liu, Xi; Li, Xiao-Lan; Cheng, Zhiping; Su, Zhiheng; Zhang, Jian; Lu, Yi; Guo, Hongwei (Frontiers in Pharmacology, 2021)
Litchi seeds have been traditionally used in Chinese herbal formula for urologic neoplasms including prostate cancer (PCa). However, the effective components of Litchi seeds and the mechanisms of their actions on PCa cell growth and metastasis remain unclear. In this study, we investigated the effects and molecular mechanisms of the Total Flavonoid of Litchi Seed (TFLS) in PCa PC3 and DU145 cell lines. We found that TFLS significantly inhibited the PCa cell proliferation, induced apoptosis, and prevented cell migration and invasion. Furthermore, we observed that TFLS upregulated the expression of epithelial biomarker E-cadherin and downregulated mesenchymal biomarker Vimentin. TFLS also increased the expression of cleaved-PRAP and Bax, and decreased the expression of Bcl-2 in both PC3 and DU145 cells. Besides, TFLS inhibited AKT signaling pathway by reducing the phosphorylation of AKT and activities of downstream signal transducers including mTOR, IκBɑ and NF-kB. Finally, TFLS treated mice exhibited a significant decrease in tumor size without toxicity in major organs in vivo. These results indicated that TFLS could suppress PCa cell growth in vivo and inhibit PCa cell proliferation and metastasis in vitro through induction of apoptosis and phenotypic reversal of EMT, which may be achieved by inhibiting the AKT/ mTOR and NF-κB signaling pathways. Taken together, our data provide new insights into the role of TFLS as a novel potent anti-cancer agent for the treatment of PCa.